Secure data management 9th VLDB Workshop, SDM 2012, Istanbul, Turkey, August 27, 2012. proceedings - Petković, Milan; Jonker, Willem (Lecture notes in computer science, 2012)
This book constitutes the refereed proceedings of the 9th VLDB Workshop on Secure Data Management held in Istanbul, Turkey, in August 27, 2012. The 12 revised full papers presented were carefully reviewed and selected from 22 submissions. The papers are organized in topical sections on privacy protection, access control, secure storage on the cloud, and trust on the Web.